La Fronde’s feminist chronicles. Feminist Associative movementis in the turn-of-the century Paris - Luengo López, Jordi (Hispania Nova, 2020)
La Fronde (1897-1905) was founded by Marguerite Durand (1864-1936) as a women-only project in which women were paid the same wage as men, and were in charge of writing, managing and distributing it. The topics covered touched on the improvement of women’s conditions in French society and the section “Chronique féministe” covered all topics related to reporting injustices suffered by women, fighting for their rights and helping women achieve full citizens’ status. Moreover, those chronicles enable us to understand what associations existed at the turn of the century in Paris, as well as the positioning of the feminist daily towards them and others from abroad.